1998
DOI: 10.1515/crll.1998.082
|View full text |Cite
|
Sign up to set email alerts
|

Surgery on Ricci positive manifolds

Abstract: We consider performing surgery on Riemannian manifolds with positive Ricci curvature. We nd conditions under which the resulting manifold also admits a positive Ricci curvature metric. These conditions involve dimension and the form taken by the metric in a neighbourhood of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 2 publications
0
31
0
Order By: Relevance
“…Using this isometry as the trivialisation of the normal bundle, they show that the manifold resulting from the surgery has positive Ricci curvature provided the dimension of the surgery is at least one, the codimension at least three, and the ratio of the radius of the sphere to the radius of the disk is sufficiently small. This result was developed further in [19] where it was shown that under the same metric assumptions, Ricci positivity can be preserved if different trivialisations of the normal bundle are used. This generalisation comes at the expense of tighter dimensional requirements, but being able to work with different trivialisations of the normal bundle is vital for applying the results to the construction of homotopy spheres.…”
Section: Surgerymentioning
confidence: 94%
See 4 more Smart Citations
“…Using this isometry as the trivialisation of the normal bundle, they show that the manifold resulting from the surgery has positive Ricci curvature provided the dimension of the surgery is at least one, the codimension at least three, and the ratio of the radius of the sphere to the radius of the disk is sufficiently small. This result was developed further in [19] where it was shown that under the same metric assumptions, Ricci positivity can be preserved if different trivialisations of the normal bundle are used. This generalisation comes at the expense of tighter dimensional requirements, but being able to work with different trivialisations of the normal bundle is vital for applying the results to the construction of homotopy spheres.…”
Section: Surgerymentioning
confidence: 94%
“…The statements we give below are slightly different to those presented in [19], so as to emphasize the metric features which we will need in the sequel. Theorem 3.2 Given E D D n S m , a constant 2 .0; 1/ and a choice of connection r , there is a constant 0 2 .0; 1/, 0 D 0 .n; m; ; r/, and a constant R 0 2 .0; 1=4/ independent of all parameters, such that for any choice of 0 Ä 0 there exists a number a D a.n; m; ; 0 / > 2 depending smoothly on 0 , with a !…”
Section: Surgerymentioning
confidence: 94%
See 3 more Smart Citations